219k views
4 votes
Prove the alternate segment theorem​

1 Answer

9 votes

Step-by-step explanation:

-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-

∠TAB = x°

∠TAC = 90°

(Angle between tangent and radius)

-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-

∠CAB = a = 90 - x

∠CBA = 90°

(Angle in a semi circle)

∠ACB = 180 - 90 - a (3ʳᵈ angle of triangle)

-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-'-

User Tereks
by
4.5k points